Improving the students’ writing proficiency through collaborative writing Method - Ismail Ismail; Ramadhan Ramadhan (Majesty Journal, 2019)
This study aimed to improve students’ writing proficiency through the collaborative writing method at SMA Muhammadiyah Kalosi, Enrekang Regency. The research employed Classroom Action Research conducted in two cycles. The participants were 35 eleventh-grade students. Both quantitative and qualitative data were collected through writing tests, observation, questionnaires, interviews, and diary notes. The writing assessment focused on students’ performance in narrative and recount texts, particularly in the aspects of orientation, complication or events, and resolution or re-orientation. The findings showed a continuous improvement in students’ writing achievement across the cycles. The mean score increased from 61.92 in the preliminary stage to 68.63 in Cycle I and reached 76.66 in Cycle II. The improvement from the preliminary stage to Cycle II was 14.74%. Students’ classroom participation also increased, from 57%–66% in Cycle I to 67%–80% in Cycle II. The results indicate that collaborative writing helped students generate ideas, organize text structure more effectively, and participate more actively in the writing process. The study concludes that collaborative writing is an effective method for improving students’ writing proficiency, especially in composing narrative and recount texts.